2015
DOI: 10.1128/aac.01464-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pharmacodynamic Evaluation of an FtsZ Inhibitor, TXA-709, and Its Active Metabolite, TXA-707, in a Murine Neutropenic Thigh Infection Model

Abstract: Antibiotics with novel mechanisms of action are urgently needed. Processes of cellular division are attractive targets for new drug development. FtsZ, an integral protein involved in cell cytokinesis, is a representative example. In the present study, the pharmacodynamic (PD) activity of an FtsZ inhibitor, TXA-709, and its active metabolite, TXA-707, was evaluated in the neutropenic murine thigh infection model against 5 Staphylococcus aureus isolates, including both methicillin-susceptible and methicillin-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Consequently, a new prodrug (TXA709, Figure ) of a different FtsZ‐targeting benzamide compound (TXA707, Figure ) arose in recent years and proved to have metabolic stability, good pharmacokinetic properties, and high in vivo potency versus MRSA . In addition, combination of TXA709 with cefdinir was demonstrated to be effective and synergistic …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a new prodrug (TXA709, Figure ) of a different FtsZ‐targeting benzamide compound (TXA707, Figure ) arose in recent years and proved to have metabolic stability, good pharmacokinetic properties, and high in vivo potency versus MRSA . In addition, combination of TXA709 with cefdinir was demonstrated to be effective and synergistic …”
Section: Introductionmentioning
confidence: 99%
“…Some exhibit potent antibacterial activity with minimum inhibitory concentration (MIC) at the micromolar range. PC190723 (Figure , top left) and its prodrugs 1a , 1b , and benzamide 2 have been demonstrated to exhibit in vitro and in vivo efficacy in a murine infection model. Moreover, X-ray crystallographic analysis revealed that PC190723 binds to a narrow cleft formed by the H7, T7 loop, and C-terminal β sheet (Figure , black oval) .…”
Section: Introductionmentioning
confidence: 99%
“…Combination of 22 with imipenem markedly reduced (by 10×) the frequency of resistance mutation to 22 . The mechanism of 22 is stabilization of the FtsZ structure resulting in a deformed Z-ring. As a consequence of the poor solubility (and lack of oral availability) of 22 , , extensive efforts were made toward the optimization (both as structures and as prodrugs) of the PC190723 class . Among the former are the benzodioxane-containing structure ( 23 ), the more potent PC190723-derived structure 24 , and the imide pro-drug 25 of a second PC190723-derived structure (the active metabolite is TXA-707, structure 26 ) .…”
Section: Resistance Mechanisms Of S Aureus Against the β-Lactamsmentioning
confidence: 99%
“…The mechanism of 22 is stabilization of the FtsZ structure resulting in a deformed Z-ring. As a consequence of the poor solubility (and lack of oral availability) of 22 , , extensive efforts were made toward the optimization (both as structures and as prodrugs) of the PC190723 class . Among the former are the benzodioxane-containing structure ( 23 ), the more potent PC190723-derived structure 24 , and the imide pro-drug 25 of a second PC190723-derived structure (the active metabolite is TXA-707, structure 26 ) . Pairing of 26 with each β-lactam within a panel of clinically used β-lactams confirmed a synergistic interaction and further showed that the β-lactams that gave the best synergy targeted preferentially S. aureus PBP2 (imipenem and cefnidir). , Prodrug 25 (structure code TXA709) completed a phase 1 clinical trial .…”
Section: Resistance Mechanisms Of S Aureus Against the β-Lactamsmentioning
confidence: 99%